(untitled) (Journal of the College of Basic Education, 2022)
The research is based on tracing a grammatical problem that we see as small in size but deep in its origin, which was put forward by grammarians in their writings, old and new, related to the corners of the attribution (the predicate and the ascribed to it) in the Arabic sentence and the change in grammatical ranks or lack of attribution followed by a difference in significance based on That attribution and its meaning. The problem is centered in the occurrence of the subject, a description similar to the verb from a subject, object or other, apply that similar in terms of action and commit to performing the same grammatical function that the verb performs from raising a subject or accusative object and stood oscillating between two important roles in the Arabic sentence, either (it is a predicate) verb), or a predicate (subjunctive), which of the two prevails over the other? This is what we will try to clarify.